THE CORRELATION BETWEEN READING HABIT AND NARRATIVE TEXT WRITING ABILITY OF THE ELEVENTH-GRADE STUDENTS OF SMAN 1 KEDIRI IN ACADEMIC YEAR 2021/2022 - Ni Luh Putu Rika Wardani; Anak Agung Putri Maharani; I Komang Budiarta (Journal on Studies in English Language Teaching (JOSELT), 2022)
The study aims at figuring out whether or not there is a significant correlation between reading habit and narrative text writing ability of the eleventh-grade students of SMAN 1 Kediri in academic year 2021/2022. The samples, 60 students total, were selected using the cluster random sampling approach. The researcher employed a questionnaire to determine reading habits and a text construction test to determine the writer's aptitude for narrative texts. Using the SPSS 26.0 application, the researcher examined the data that had been gathered. The data were distributed normally and homogeneous, according to the results of the normality and homogeneity test. Additionally, the rcounted was greater than the rtable at 0.859. This indicates that the two variables had a correlation. The t-test also revealed that the tcounted was higher than the ttable, which was 60.161 > 1.672. Furthermore, based on the data analysis, the researcher concluded that there was a significant correlation between reading habit and narrative text writing ability of the eleventh-grade students of SMAN 1 Kediri in academic year 2021/2022.